Between the Motherhood and Career Gripper: A Case Study of First-Time Mother - Aysun Doğutaş (Skad)
Many women confront complex challenges when juggling motherhood with a profession, especially those who are starting their parenting journey for the first time. This case study explores Aisa's experiences as a first-time mother juggling her responsibilities as a caretaker with her desire to pursue a career in the business world. This study examines the complex dynamics, emotional challenges, and coping strategies used by a first-time mother as she tries to balance the demands of motherhood with her career goals through qualitative analysis of participant observations, semi-structured interviews, and field notes. Four themes have surfaced following the comprehensive data analysis. These themes include doubting her role as a mother, putting off her job goals, feeling guilty, and giving up on herself. The results highlight the complex interactions that exist between personal objectives, support networks, and society expectations, shedding light on the challenges that come with trying to strike a happy balance between motherhood and work. This study adds to a better knowledge of the difficulties faced by first-time mothers by providing insights into their lived experiences. It also helps develop strategies for empowering and supporting these women in both family and work settings.